2016
DOI: 10.1039/c6ra10909h
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of different surface sites with silicon chlorides during atomic layer deposition of silicon nitride

Abstract: The reactivity of surface sites plays a very important role to determine the thermodynamics and kinetics of ALD processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 59 publications
3
38
0
Order By: Relevance
“…By introducing the H2 plasma before the N2 plasma, efficient ligand removal from the surface can be achieved by H radicals with a long lifetime. The SiNx films with an excellent step coverage and wet etch rate were obtained [21][22][23][24]. The wet etch rate (WER) test was performed to investigate SiN x etching properties.…”
Section: Characteristics Of Sin X Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing the H2 plasma before the N2 plasma, efficient ligand removal from the surface can be achieved by H radicals with a long lifetime. The SiNx films with an excellent step coverage and wet etch rate were obtained [21][22][23][24]. The wet etch rate (WER) test was performed to investigate SiN x etching properties.…”
Section: Characteristics Of Sin X Thin Filmsmentioning
confidence: 99%
“…The PEALD of SiN x using aminosilane and NH 3 plasma leads to a reduced growth rate because the H-and NH x -terminated surface is not undercoordinated, which in turn inhibits precursor adsorption. In contrast, N 2 plasma is able to generate reactive undercoordinated bare surface sites; PEALD using aminosilane and N 2 plasma reveals quite sensible growth rates [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The findings are consistent with prior work that employed tetraiodosilane and titanium tetraiodide to generate Ti-Si-N diffusion barriers for copper metallization at low temperatures. 73 In terms of the PE-ALD adsorption and decomposition mechanisms for inorganic sources, one relevant report 82 analyzed the reactivity of β-Si 3 N 4 surface sites with Si 2 Cl 6 (using SiH 4 as comparative baseline) during the PE-ALD Si 2 Cl 6 substrate exposure step by combining ab initio density functional theory calculations with actual PE-ALD SiN x film deposition. The analysis examined three types of substrate surface sites: (a) hydrogen passivated N and Si sites (NH/SiH); (b) NH and SiNH 2 sites formed during the NH 3 exposure step (NH/SiNH 2 ); and (c) under-coordinated bare Si=N sites.…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%
“…These findings led to the identification of a 3 step PE-ALD process to attain the most energetically favorable surface sites during the Si source PE-ALD substrate exposure step. 82 Another investigation 11 also explored the role of a N 2 plasma pre-treatment prior to the SiH 4 exposure step on Si substrates and found that atomic N and N + are the central reactant species that adsorb to the Si surface to form Si-N. The latter then act as reactive adsorption spots for SiH 4 at N dangling bond sites, generating adsorbed SiH x and NH x species.…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%
“…NH 3 is considered a good alternative reactant, and has eventually become the most widely used reactant for SiN x thermal ALD. As shown in Table 1 , several chlorosilane precursors including SiCl 4 , SiH 2 Cl 2 , Si 2 Cl 6 and Si 3 Cl 8 have been extensively investigated for SiN x thermal ALD [ 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. It is also particularly important to point out the fact that SiN x thermal ALD using non-chlorosilane-based precursors has not yet been reported.…”
Section: Current Research Progressmentioning
confidence: 99%